Perceptual Mapping of Higher Education Prospective Students in Bandung, Indonesia: A Base for a Strategy - Zulganef (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at analyzing the position of some universities in Bandung, especially the position of Widyatama University. The analysis was conducted through perceptual mapping created through a technique called multidimensional scaling (MDS). The position of higher education is mapped based on 8 attributes and 7 colleges as references in the perceptual map. Based on 8 perceptual map attribute preferences and the position of each university, the author analyzed competitive advantages and disadvantages and similarities amongst the universities. The sample size is 750 respondents. The respondents are prospective students of higher education. This paper also discusses the results of the research and makes some recommendations.